Induksi Umbi Mikro Kentang Secara In Vitro Pada Suhu Tinggi Dengan Beberapa Tuber Promoter - Usman Kris Joko Suharjo; Bambang Gonggo Murcitro; Tunjung Pamekas; Haryuni Haryuni (Biogenesis: Jurnal Ilmiah Biologi, 2017)
Potato microtubers are the miniature of conventional seed tubers grown in the field. Producing potato microtuber in vitro at high temperature by applying many kinds of tuber promoting substances is similar to producing potato in the field at low elevation by applying the same tuber promoting substances. The objective of this research was to evaluate the performance of seven tuber promoters in inducing potato microtubers at high temperatures. Micro cuttings (6 weeks old) were grown at the liquid media of MS for stolon induction. Six weeks afterward, the media were moved to microtuber inducing media supplemented with tuber promoters ((FD, FD+10 COU, FD+20 COU, FD+30 COU, FD+40 COU, FD+50 COU, and IPB). The media were incubated in the dark at 20 + 2oC and 29 + 2oC. The results showed that, in general, high temperature inhibited crop growth and tuber formation. Individually, tuber promoter formula significantly affected microtuber emergence, in which IPB showed the slowest treatment in producing microtubers, the smallest number of tuber produced, and the smallest size of tubers. The interaction between temperature and tuber promoters were significantly affected the tuber formation, in which the fastest tuber formation (7,0 days ) was found in FD + 40 COU and the highest  percentage of plant producing tubers was found in FD + 30 COU. Moreover, the highest number of microtuber and the heaviest weight of microtuber were found in FD (no Coumarin). It was safely concluded that all tuber promoters were best performed at low temperature. Should anyone wish to make those tuber promoters work better at high temperature, it is recommended to increase the concentration of Coumarin added to the formula of tuber promoting substances.